Formal techniques for safety-critical systems : third International Workshop, FTSCS 2014, Luxembourg, November 6-7, 2014. Revised selected papers /: third International Workshop, FTSCS 2014, Luxembourg, November 6-7, 2014. Revised selected papers. (2015) - Unknown
No abstract available